Study on Remote Sensing Retrieval of Soil Moisture in Arid Desert Area Based on FTVDI. Issue 1 (July 2021) - Lu, Zhao; Wang, Daqing; Ding, Zhibin; Shi, Yue; Ning, Hao; Zhao, Jiazheng; Zhao, Hongfei; Cui, Huiru; Xu, Haoli; Cheng, Zijian; Zhao, Xiaoning
Abstract: In this study, the desert oasis area of Minqin, Gansu Province was taken as the study area, and China Gaofen-6(GF-6) satellite and China-Brazil Earth Resource Resources Satellite - 04 (CBERS-04) were invlked as remote sensing data sources. The soil moisture was retrieved by using Forward Temperature Vegetation Dryness Index (FPVDI), and the spatial distribution of soil moisture was analyzed. The result showed that FTVDI could be directly and accurately retrieve soil moisture.